(untitled) (Fiep Bulletin - online, 2020)
Abstract: Anxiety derives from stressors making people have a chance to thrill and change behavior. A dance as a physical experience can have common stress episodes from day to day. The objective of this study was to determine the level of anxiety and stress in fitness and sedentary women practitioners from the Joinville region. The IDATE - State Trait Anxiety Inventory formulated by Spielberger et al. (1970) translated into Biaggio and Natalício (1979) for the Brazilian population, as a protocol to measure the degree of anxiety and stress. The same was applied to 60 women, a group of fitness (30) and sedentary (30), with a mean age of 34.5 ± 9.6. The result was 56.67% of the practitioners with high level of anxiety-state and 53.33% of the sedentary high level high. Concerning anxiety-trait, 60% of the practitioners are in a moderate high level and in 50% of the sedentary level high. The sedentary women are 19.8% (p = 0.0008) higher than those of fitness dance practitioners. The anxiety-trait level of sedentary women is 22.9% (p = 0.001) higher than those who practice it. Age does not interfere with results. Based on the collected data, it can be affirmed that, as the dance practitioners are conditioned, they have levels of anxiety and stress lower than the sedentary women.